2020
DOI: 10.3390/healthcare8010048
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Deep Vein Thrombosis in Gynecologic Cancer Survivors with Lower Extremity Edema: A Single-Center and Retrospective Study

Abstract: This study was conducted to examine predictive factors of deep vein thrombosis (DVT) in gynecologic cancer survivors with lower extremity edema (LEE). In the current single-center, retrospective study, there was a total of 315 eligible patients, including 80 patients with DVT and 235 without DVT. They were therefore divided into two groups: the DVT group (n = 80) and the non-DVT group (n = 235). Then, baseline and clinical characteristics of the patients were compared between the two groups. In our study, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…However, retrospective research analyzed 135 gynecological cancer survivors and found that the incidence of DVT in lower limbs was 25.4%. 27 Undeniably, the varied study design standards and the dearth of multicenter or big sample data studies may be to blame for these differences. In addition, 14 DVT patients developed pulmonary embolism in our research.…”
Section: Discussionmentioning
confidence: 99%
“…However, retrospective research analyzed 135 gynecological cancer survivors and found that the incidence of DVT in lower limbs was 25.4%. 27 Undeniably, the varied study design standards and the dearth of multicenter or big sample data studies may be to blame for these differences. In addition, 14 DVT patients developed pulmonary embolism in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, after the distant metastasis, tumor cells interact with the hemostatic system, which emphasizes that hypercoagulability already exists in patients with localized cancer spread. 55 Studies have shown that detecting cancer at an early stage can significantly improve the chances of survival. However, over 50% of cancer cases are diagnosed at an advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the risk of DVT in women undergoing gynecologic surgery is estimated to be between 17-40%. 55 The relationship between gynecologic cancers and thrombotic events is believed to be linked to lymphadenectomy and venous congestion caused by tumors or enlarged lymph nodes. 70 Lymphadenectomy is a frequently utilized procedure in the evaluation of lymph node status and staging of gynecologic malignancies, as well as a therapeutic intervention for patients with gynecologic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation